2015
DOI: 10.1093/neuonc/nov186
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive functioning and health-related quality of life in patients treated with stereotactic radiotherapy for brain metastases: a prospective study

Abstract: Prior to SRT, neurocognitive functioning and HRQoL are moderately impaired in patients with brain metastases. Lower baseline KPS and larger tumor volume are associated with worse functioning. Over time, SRT does not have an additional detrimental effect on neurocognitive functioning and HRQoL, suggesting that SRT may be preferred over whole-brain radiotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
110
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(137 citation statements)
references
References 41 publications
17
110
10
Order By: Relevance
“…OS, overall survival; EGFR, epidermal growth factor receptor; ALK, anaplastic lymphoma kinase; SRS, safety of stereotactic radiosurgery; WBRT, whole brain radiotherapy; CI, confidence interval. SRS generally has advantages when compared with WBRT in terms of safety, such as the late development of cognitive dysfunction and alopecia, which could affect patients' quality of life (20)(21)(22)(23)(24)(25). Yamamoto et al reported the safety and feasibility of SRS for ten or more BMs when compared to the patients with less lesions (11) In addition SRS can be applied repeatedly for BMs and can be performed in a shorter time, resulting in a reduced burden on patients.…”
Section: Discussionmentioning
confidence: 99%
“…OS, overall survival; EGFR, epidermal growth factor receptor; ALK, anaplastic lymphoma kinase; SRS, safety of stereotactic radiosurgery; WBRT, whole brain radiotherapy; CI, confidence interval. SRS generally has advantages when compared with WBRT in terms of safety, such as the late development of cognitive dysfunction and alopecia, which could affect patients' quality of life (20)(21)(22)(23)(24)(25). Yamamoto et al reported the safety and feasibility of SRS for ten or more BMs when compared to the patients with less lesions (11) In addition SRS can be applied repeatedly for BMs and can be performed in a shorter time, resulting in a reduced burden on patients.…”
Section: Discussionmentioning
confidence: 99%
“…Baseline characteristics of patients with baseline HRQoL scores were not reported in two studies [39,40]. For two studies [33,36], a proportion of patients was also included in a subsequent study (respectively [32,37]). Sample sizes in the 9 selected studies ranged from 15 to 97 patients.…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
“…In most studies, patients were female (range 43.2 to 67.3%), had primary lung cancer (range 37.3 to 100%), and had a median Karnofsky Performance Status (KPS) score of 80 (range < 70 to 100) ( Table 1). In four studies [34][35][36][37], patients with newly diagnosed BM were included; in four other studies [32,33,38,39], patients received prior BM treatment; and in one study [40], it was not reported if patients received prior BM treatment. Reasons for dropout were not reported in 6 studies [32,34,35,[38][39][40], and in two studies [36,37], reasons of dropout were reported, but without the numbers of patients (Table 1).…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
“…Whole body irradiation [23], whole brain irradiation with low [24] or high LET rays [25] and stereotactic radiosurgery [26] have all been shown to be able to induce cognitive dysfunction in rodents. Nonetheless, WBI with X-ray or γ-ray is the main modality to treat brain tumors in current clinical practice.…”
Section: Irradiation Dose In Cognitive Testsmentioning
confidence: 99%